Symptomatic response to GERDOFF® in patients with gastro-esophageal reflux disease and poor response to alginates: an exploratory, post-market, open-label study - Boarino, Valentina; Raguzzi, Ivana; Marocchi, Margherita; Merighi, Alberto (Turkish Journal of Gastroenterology, 2020)
Background/Aims: A novel medical device based on hyaluronic acid, chondroitin sulphate plus aluminum hydroxide (GERDOFF®, melt-in-mouth tablets) showed efficacy in reducing GER-related symptoms. This exploratory, open-label study evaluated symptomatic effects of a 14-day treatment with GERDOFF® in GERD patients. Materials and Methods: GERD Impact Scale (GIS) questionnaire was filled at baseline visit, after 7 and 14 days of treatment; patients’ Global Satisfaction was evaluated at the final visit. Primary endpoint was the reduction of heartburn episodes per week; secondary endpoints were GERD-related symptoms, patients’ satisfaction, and safety. Results: Forty patients were included, 22 were on stable therapy with proton pump inhibitor (PPI). Compared to baseline, the days with heartburn episodes and the GIS score progressively decreased during the first (p<0.0001) and the second week of treatment (p<0.0001). Heartburn episodes per week (p<0.0001) and the GIS score (p<0.0001) decreased in the first and the last 7 days of 14-day treatment and did not differ between patients on and off PPI. The treatment was safe and well-tolerated, and it was rated as very good (46.2%) or good (43.6%) on the satisfaction questionnaire. Conclusion: GERDOFF® could effectively treat GER symptoms in patients not responding to PPI or alginate-based formulation. ISRCTN_15143752.